Neighborhood story. 2 - Yazawa, Ai, 1967- (Shojo beat manga., 2024)
"Mikako aims to take the world of fashion by storm but stumbles when love comes into season in this coming-of-age tale from the creator of Nana! Welcome to Happy Berry! No, this isn't a fruit stand, but the label dreamed up by aspiring fashion designer Mikako Koda. In her quest to make a name for herself in the fashion world, Mikako enters Yazawa Arts Academy, a prestigious art school, alongside her strictly platonic childhood friend Tsutomu. But there's one problem--Tsutomu's uncanny resemblance to a rock star skyrockets him to popularity and leads him to date the prettiest girl in school. Now Mikako can't help but wonder if what she feels is jealousy. As Mikako and her friends work hard to get their club up and running, Mikako notices Tsutomu has gotten close to their new member, Ayumi, and begins to grow jealous. Later, Tsutomu and Mikako celebrate their birthdays, but Mikako's father's absence weighs heavily on her heart, prompting Tsutomu to urge her to track him down. Will this long-overdue reunion lead to a breakthrough for Mikako, or is nothing she can do extreme enough to force her to unbottle her emotions?"--Publisher.